The Linkage of Ecomonics and Sociology in the Analytical Paradigm of Social Science, or the Explication of Max Weber's Interpretive Sociology in the Zenonas Norkus' Methodological Model of Rational Choice - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2003)
Review: Norkus, Zenonas. 2003. Max Weber ir racionalus pasirinkimas. Vilnius: Margi raštai.